MINIMIZING TURNOVER INTENTION STRATEGY: The Role of Transformational Leadership, Intrinsic Motivation, and Job Satisfaction - Daeli, Azizah Siti (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The high turnover intention rate in the current work environment poses a serious challenge for organizations. Therefore, this study aims to investigate effective strategies to minimize turnover intention, focusing on the role of transformational leadership, intrinsic motivation, and job satisfaction. The research aims to explore the relationships between transformational leadership, intrinsic motivation, job satisfaction, and turnover intention. With a deep understanding of these factors, concrete strategies to reduce turnover intention in the workplace are expected to be identified. The study employs a quantitative approach through surveys and statistical analysis to collect and analyze data from respondents who are members of organizations. The research instruments include measurement scales for transformational leadership, intrinsic motivation, job satisfaction, and turnover intention. Data analysis reveals significant findings regarding the positive relationship between transformational leadership and intrinsic motivation with job satisfaction. Furthermore, job satisfaction is found to be negatively correlated with turnover intention. The practical implications of these findings underscore the need for organizations to adopt transformational leadership styles and enhance intrinsic motivation among employees to increase job satisfaction and decrease the intention to switch jobs.